Taking Action in Teacher Education: Social Studies as a Means of Cultivating Engaged Citizenship (LEARNing Landscapes, 2014)
Social Studies was introduced into the Ontario curriculum in 1937, integrating history and geography, but also various matters pertaining to law, government, and civics, as a means of focusing students’ attention on the world around them thoughtfully and critically. Informed by the past, students were directed to gaze upon the future and to take action within their communities. Civic engagement and Social Studies were very closely linked. This essay argues that Social Studies education has a particular role to play in teacher education, as a medium of cultivating meaningful experiences relating to contemporary life and as a means of exploring the disciplinary roots of the subject. Teacher education is explored as a site for "take action" projects, which relate citizenship, historical thinking, and social action.
Keywords: social studies; curriculum; history; geography; civic engagement; experience; teacher education; citizenship; action